2020
DOI: 10.1038/s41533-020-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary care management of asthma: do we know what really works?

Abstract: Asthma imposes a substantial burden on individuals and societies. Patients with asthma need high-quality primary care management; however, evidence suggests the quality of this care can be highly variable. Here we identify and report factors contributing to high-quality management. Twelve primary care global asthma experts, representing nine countries, identified key factors. A literature review (past 10 years) was performed to validate or refute the expert viewpoint. Key driving factors identified were: polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 78 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…Heavy workload and inadequate training were two important barriers to low adherence by primary care doctors to the guidelines [ 23 ]. Clinical pathway and supporting educational materials can be created and used to translate the evidence-based guidelines into succinct algorithms and facilitate the asthma care by primary care doctors [ 24 , 25 ]. Effective asthma self-management requires a comprehensive approach comprising of patients’ education and resources, professional skills and motivation and organisation priorities and routines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy workload and inadequate training were two important barriers to low adherence by primary care doctors to the guidelines [ 23 ]. Clinical pathway and supporting educational materials can be created and used to translate the evidence-based guidelines into succinct algorithms and facilitate the asthma care by primary care doctors [ 24 , 25 ]. Effective asthma self-management requires a comprehensive approach comprising of patients’ education and resources, professional skills and motivation and organisation priorities and routines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of an asthma app may not yield information regarding the quality of the asthma content presented in the app with respect to the clinical or scientific literature. Prior studies have observed variability in the quality of asthma information with respect to its consistency with National Asthma Education and Prevention Program guidelines [ 3 ]. Future studies should examine the concordance between asthma education and asthma management clinical tools within popular asthma apps.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors combine to contribute to poor asthma rates and worsen outcomes. Provider practice behaviors, suboptimal access to health care, lack of patient knowledge regarding proper medication use, and patients’ difficulty adhering to medical regimens contribute to poor asthma outcomes [ 3 - 8 ]. With appropriate medical care including education, patients can achieve asthma control; however, there are competing challenges to providing effective patient education, such as time constraints and prioritizing other issues above asthma education [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Setting up a team in primary health care asthma control has improved globally in recent decades, however, in spite of the availability of effective treatments, it remains sub-optimal 25 and it is a substantial reason for direct and indirect costs. 26 Uncontrolled asthma affects a significant ManaGinG aSTHMa in PHc cOrreia-de-SOUSa vol. 112 -no.…”
Section: The Importance Of the Primary Health Care Team For The Follo...mentioning
confidence: 99%